Noble Metal-Free Hierarchical ZrY Zeolite Efficient for Hydrogenation of Biomass-Derived Levulinic Acid - Hu, Di; Xu, Hong; Wu, Zuotong; Zhang, Man; Zhao, Zhiyue; Wang, Yuchen; Yan, Kai (Frontiers in Chemistry, 2021)
Developing a low-cost and robust catalyst for efficient transformation of biomass-derived platform chemicals plays a crucial role in the synthesis of future transportation fuels. Herein, post-synthetic strategy was employed to develop a noble-metal free and robust ZrY zeolite catalyst, which is efficient for the hydrogenation of biomass-derived levulinic acid (LA) into biofuels γ-valerolactone (GVL), whereas, over 95% yield of GVL was achieved in 10 h at 220 oC. The effects of acidic properties from ZrY catalysts and various reaction parameters on the catalytic performance were then discussed in details. Subsequently, different characterization tools were used to compare the difference and relationship of structure-activity between the fresh and spent ZrY catalysts. It was found acidity and metal-support interaction were important for the direct synthesis of GVL. This works provides a guideline to design noble-metal free catalyst for high-value utilization of biomass-derived sources.